In search of moral foundations of law: debate on nature of inclusive legal positivism - A. B. Didikin (Omsk State Technical University, Federal State Budgetary Educational Institution of Higher Education, 2021)
The paper is devoted to the analysis of the arguments of foreign jurists about the nature and advantages of inclusive legal positivism as a legal theory that justifies the existence of moral foundations of the legal system. Examples from judicial practice are considered, as well as key theoretical approaches that reveal the necessary and sufficient features of inclusive legal positivism, as well as its subject specifics and basic provisions on the relationship between law and morality. The paper is prepared within the framework of the HSE research project «Applied Ethics».